NVH and reliability analyses of the engine with different interaction models between the crankshaft and bearing. (1st January 2016) - He, Zhenpeng; Gong, Wenqin; Xie, Weisong; Zhang, Junhong; Zhang, Guichang; Hong, Zhenyu
Highlights: Different interaction models are employed to analyze engine NVH and reliability. The EHD model considering cavitation is used to predict the NVH and reliability. Rigid crankshaft model overestimates or underestimates the bearing load capacity. The pressure distribution difference is reason for the dynamic and NVH difference. Abstract: The precision of the interaction model is very important to predict NVH and the reliability of an internal combustion engine. The interaction model between the crankshaft and the bearing is hard to be established precisely due to its complex interaction relationship and dynamic characteristic. In this paper, the elasto-hydrodynamic lubrication model with cavitation theory is built to couple with multi-body dynamic theory to analyze the noise and reliability of the engine, the results were compared with nonlinear spring model and hydrodynamic lubrication model based on a typical in-line six cylinder engines, such as load carrying capacity of the bearing, velocity level of the engine surface, noise level of engine surface and stress of the crankshaft. The results showed that the vibration, noise and stress prediction difference is due to the exciting of the oil film pressure distribution, rigid and flexible body that is used to build the dynamic model will lead the load capacity of the bearing to be great different. Nonlinear spring model and hydrodynamic lubrication model are precise enough to predict the vibration or noise. The All the analysis will provide the guidance for the engine NVH optimization and structural reliability design.